Flora of Bahia: Acalypha (Euphorbiaceae) - Bomfim, Airã de Lima; Santos Carneiro-Torres, Daniela (SITIENTIBUS série Ciências Biológicas, 2022)
A floristic survey of Acalypha (Euphorbiaceae) from Bahia state, Brazil, is presented. Nine native species are recognized: Acalypha almadinensis, A. amblyodonta, A. brasiliensis, A. communis, A. inselbergensis, A. klotzschii, A. multicaulis, A. poiretii, and A. villosa; as weel as the cultivated A. wilkesiana. Identification key, descriptions, illustrations, general comments, and species distribution maps in Bahia are provided.